2011
DOI: 10.4049/jimmunol.1001563
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Potentiates Human Lung Mast Cell Tissue Plasminogen Activator Activity

Abstract: We investigated whether adenosine, a potent contributor to the regulation of pulmonary function, can modulate human lung mast cell (HLMC) fibrinolytic activity. Tissue plasminogen activator (tPA) activity and tPA transcript expression levels from a human mast cell line (HMC-1) and HLMC were monitored following adenosine application. Adenosine potentiated mast cell tPA activity and tPA gene expression in a dose-dependent manner. Adenosine effects were abolished in the presence of adenosine deaminase. HMC-1 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Earlier reports showed that adenosine A 2 receptor activation promotes plasminogen activator release in rabbit alveolar macrophages [8], and the adenosine A 2A receptor subtype is responsible for increased tPA expression and activity in lung mast cells [9]. In addition, intra-arterial infusions of ATP, an adenosine precursor, to healthy volunteers induce tPA release [10].…”
Section: Introductionmentioning
confidence: 98%
“…Earlier reports showed that adenosine A 2 receptor activation promotes plasminogen activator release in rabbit alveolar macrophages [8], and the adenosine A 2A receptor subtype is responsible for increased tPA expression and activity in lung mast cells [9]. In addition, intra-arterial infusions of ATP, an adenosine precursor, to healthy volunteers induce tPA release [10].…”
Section: Introductionmentioning
confidence: 98%
“…Because of the difficulty in obtaining sufficient human lung derived mast cells for genetic profiling, we have chosen to employ the HMC-1 human mast cell line as model. Our choice of these cells rather than the LAD2 human mast cell line or human cord blood derived mast cells was based on the following considerations: HMC-1 cells express endogenously the A2a, A2b and A3 adenosine receptors, which are also expressed by mast cells from most species (Hua et al, 2011); others (Feoktistov et al, 2003) and us (Baram et al, 2010) have previously shown that HMC-1 cells expresss a funcational A3R; in a similar fashion to human lung mast cells, HMC-1 cells produce VEGF in response to NECA, unlike the LAD2 cells (Detoraki et al, 2009); HMC-1 and human lung mast cells interact with human lung fibroblasts (Moiseeva et al, 2013) and migrate towards Th2 stimulated airway smooth muscle that is derived from asthmatic, but not non-asthmatic, subjects (Sutcliffe et al, 2006); both cell types produce tissue-plasminogen-activator in response to adenosine (Sereda et al, 2011) and display similar anti-microbial activity (Cruse et al, 2010). Taken together with the findings that neither the LAD2 cells nor human cord blood derived mast cells recapitulate the potentiation of FcRI induced degranulation by adenosine or A3R agonists that occurs in human lung mast cells (Suzuki et al, 1998;Hua et al, 2011;Gomez et al, 2011;Leung et al, 2014), we rationalized that despite their limitations arising from the expression of a constitutively active kit receptor and lack of expression of the FcRI (Nilsson et al, 1994), HMC-1 cells are instrumental as model for deciphering the functional signature of the A3R in human lung mast cells.…”
Section: Discussionmentioning
confidence: 95%
“…As up to 20% of MCs infiltrating the bronchial epithelium in steroid-na€ ıve asthma contain chymase [106], an effect of released chymase on bronchial epithelial integrity cannot be discounted. Plasminogen activator inhibitor-1 (PAI-1) has been implicated in airway remodelling in asthma (reviewed in [599]) and is produced by both human MCs [600,601] and airway epithelial cells [602]. Following FceRIdependent activation of the human LAD2 MC line, chymase activated latent TGF-b1 secreted by MCs, which in turn induced the production of PAI-1 by bronchial epithelial cells.…”
Section: Mast Cellsmentioning
confidence: 99%
“…Plasminogen activator inhibitor‐1 (PAI‐1) has been implicated in airway remodelling in asthma (reviewed in ) and is produced by both human MCs and airway epithelial cells . Following FcεRI‐dependent activation of the human LAD2 MC line, chymase activated latent TGF‐β1 secreted by MCs, which in turn induced the production of PAI‐1 by bronchial epithelial cells.…”
Section: Mast Cell Distribution Within the Airways In Asthma – Implicmentioning
confidence: 99%